Cara mengasah rasa ingin tahu anak dalam pembelajaran matematika - Nurul Erika Putri Siregar; Yona Elya Siregar; Ridho Maulana Simatupang (ARKA INSTITUTE, 2022)
Curiosity is important in developing students' knowledge and experience, so it is necessary to create a learning climate that can create and maintain students' curiosity in learning mathematics. This study aims to examine the importance of curiosity in mathematics learning and assess the impact of Active Knowledge Sharing technique in increasing students' curiosity in an educational environment in class III-b at MIS Nurhafizah. This study uses quantitative research methods. Information was taken from the post-test results as well as questionnaires, documentation, and others. The collection technique was to give a post-test containing 15 essay questions and a questionnaire containing 20 statements to students in class III-B. The results of this study indicate that students in class III-b at MIS Nurhafizah have high curiosity about mathematics. Although female students have higher abilities, male students show greater interest in solving math problems. Based on the conclusions obtained, it is suggested to educators that in learning activities, teachers should involve students more in the learning process. So that students are more active and can improve their thinking skills.